IMPLEMENTATION OF PATCH BASED INPAINTING METHOD - Malluvalasa, S N Lakshmi (Innovare Journal of Education, 2016)
ABSTRACT Inpainting is an emerging field in image processing research area. Inpainting is the retouching process which is used to remove or change the deteriorated/destroyed parts of an image and make the image real visualization to human eye in a plausible way. Different algorithms are proposed for this image inpainting to get quality in image and also time taking to process the inpainting technique. It is more useful in the areas of digital photography, films too. Many algorithms had proposed for this inpainting method and from those algorithms Exemplar Based Inpainting has got more popularized algorithm. Different approaches had applied to get reduce the time complexities in achieving the realistic appearance of the image. In this we presenting a new approach algorithm which makes the exemplar approach will be little faster than previous algorithms by using patch-based. Keywords: Inpainting, Exemplar based, digital Photography, algorithms, image Processing